Adsorption of Pb(II) and Cd(II) by Squid Ommastrephes bartrami Melanin - Shiguo Chen; Changhu Xue; Jingfeng Wang; Hui Feng; Yuming Wang; Qin Ma; Dongfeng Wang (Bioinorganic Chemistry and Applications)
The adsorption of Cd(II) and Pb(II) by squid melanin was investigated. At a metal ion concentration of 2 mM/L, the biosorption efficiency of melanin reached 95% for Cd(II) and Pb(II). The maximum content of bound Cd(II) and Pb(II) was 0.93 mM/g and 0.65 mM/g, respectively. Temperature had no obvious effect on the adsorption of the metals, and in a pH range of 4.0–7.0, the adsorption yield was high and stable. Macrosalts such as NaCl, MgCl2, and CaCl2 had no obvious effect on the binding of Pb(II) but greatly diminished the adsorption of Cd(II), which indicated that different functional groups in squid melanin are responsible for their adsorption. IR analysis of metal ion-enriched squid melanin demonstrated that the possible functional groups responsible for metal binding were phenolic hydroxyl (OH), carboxyl (COOH), and amine groups (NH). This study reports a new material for the removal of heavy metals from low-strength wastewater.